Preventing Credit Card Fraud : a Complete Guide for Everyone from Merchants to Consumers. - Lee, Jen Grondahl (Rowman & Littlefield Publishers, 2017)
Preventing Credit Card Fraud looks at all angles of this crime and is an easily-accessible guide that everyone engaged in online purchases and sales needs to have to become better informed of what they can do and how they can keep their personal information more secure.